Sorghum grain for lactating dairy cows - C.A. Gladamez; John E. Shirley; A.J. Gallegos (Kansas Agricultural Experiment Station Research Reports, 1990)
Holstein cows in early lactation were utilized to evaluate the effects of supplementing concentrate diets of sorghum grain on milk production, milk composition, somatic cell count, and body condition. At 21 d postpartum, cows were randomly assigned to receive four concentrate diets consisting of 1) corn, 2) sorghum, 3) sorghum plus 1 lb tallow, and 4) sorghum plus wheat in a 70:30 ratio. All concentrates were combined with chopped alfalfa hay in a total mixed diet and fed twice daily. Treatments included a 7-day preliminary period and a 16-week experimental period. Cows fed the sorghum plus tallow diet produced 14% more milk than cows fed either corn or sorghum alone and 10% more than cows fed the 70:30 sorghum plus wheat diet. Milk fat was unaffected by diet, although cows receiving the sorghum plus wheat diet tended to produce milk with less fat (3.3% vs 3.5% for the other diets). Body weight and body condition tended to be higher for cows fed the sorghum plus wheat combination. The addition of tallow or wheat to grain sorghumbased diets appears to improve its value for high-producing cows.; Dairy Day, 1990, Kansas State University, Manhattan, KS, 1990; The 1990 Annual KSU Dairy Day is known as Dairy Day, 1990
Keywords: Dairy Day; 1990; Kansas Agricultural Experiment Station contribution; no. 91-148-S; Report of progress (Kansas Agricultural Experiment Station); 608; Dairy; Sorghum grain; Lactating